2018
DOI: 10.1007/s11356-018-2260-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-digestion of sewage sludge with crude or pretreated glycerol to increase biogas production

Abstract: Anaerobic co-digestion of sewage sludge and glycerol from the biodiesel industry was evaluated in three experimental stages. In the first step, the addition of higher proportions of crude glycerol (5-20% v/v) to the sludge was evaluated, and the results showed a marked decrease in pH and inhibition of methane production. In the second step, co-digestion of sludge with either a lower proportion (1% v/v) of crude glycerol or glycerol pretreated to remove salinity resulted in volatile acid accumulation and low me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The high methane yield in the latter was due to the use of optimized two-stage anaerobic digestion processes (acidogenic and methanogenic) and chemically pre-treated sewage sludge [39]. Despite the decrease in VS removal, dos Santos Ferreira, et al [40] showed that the optimum crude glycerol addition was 0.5 vol% to achieve 73% enhancement in methane yield. The pilot-scale study by Razaviarani, et al [41] showed that the optimum organic loading rate should be around 1.04 g VS L −1 d −1 , corresponding to 1.1 vol% of glycerol addition to avoid process instability.…”
Section: Crude Glycerolmentioning
confidence: 99%
“…The high methane yield in the latter was due to the use of optimized two-stage anaerobic digestion processes (acidogenic and methanogenic) and chemically pre-treated sewage sludge [39]. Despite the decrease in VS removal, dos Santos Ferreira, et al [40] showed that the optimum crude glycerol addition was 0.5 vol% to achieve 73% enhancement in methane yield. The pilot-scale study by Razaviarani, et al [41] showed that the optimum organic loading rate should be around 1.04 g VS L −1 d −1 , corresponding to 1.1 vol% of glycerol addition to avoid process instability.…”
Section: Crude Glycerolmentioning
confidence: 99%
“…The use of crude glycerol has been proposed to boost biogas production. Successful co-digestion with sewage sludge, manures, and leachates has been reported indicating increments in methane yields that can double this parameter when compared with the control [31,[91][92][93][94]. However, the excessive addition of this co-substrate can cause inhibition, which is associated with long-chain fatty acid levels in the reactor, or the accumulation of propionic acid as an intermediary from the anaerobic degradation [95].…”
Section: Co-digestion Proposed As the Best Way To Take Advantage Of Process Synergiesmentioning
confidence: 99%
“…The OLRs prior to the drop in efficiency for all treatments were generally higher than the range of OLRs that other researchers have studied for biodiesel byproducts. Most were in the range of 0.5–6.5 g COD L −1 day −1 , 10,12,16,22–24 but Ma et al 13 . demonstrated an OLR of 11.7 g COD L −1 day −1 .…”
Section: Resultsmentioning
confidence: 95%
“…The AD system is either exposed gradually to increasing concentrations of inhibitors or the organic loading rate (OLR) of the substrate is gradually increased. Research on acclimatization in anaerobic co‐digestion was mostly conducted in laboratory conditions, for better control of experimental conditions than in field conditions, using lab‐scale digesters with working volume from 50 10 to 5500 mL 11 . In some reported AD acclimatization experiments of biodiesel waste products, only a single digester was used without replicates 12,13 .…”
Section: Introductionmentioning
confidence: 99%